Medical mistrust in online cancer communities: a large-scale analysis across 10 cancer entities - Bubnoff, Fabian von; Werner, Johannes; Hebach, Nils R.; Chopra, Deepti A.; Schubert, Marc Cicero (Psycho-oncology, 2025)
Background Medical mistrust is a barrier to optimal cancer care. Analyzing social media posts where patients voice mistrust provides an opportunity to understand its variations and derive potential ways to address medical mistrust. Aims To (1) identify the frequency of mistrust expression in cancer-related Reddit posts, (2) characterize mistrusted entities and reasons for mistrust, and (3) identify emotional tone associated with mistrust. Methods 101,963 posts from 10 entity-specific cancer communities on the social media platform Reddit made before September 30, 2024, were analyzed using a Large Language Model (LLM, “gpt-4o-mini”) in this cross-sectional study. Performance of the LLM was compared to human raters. Categories for mistrusted entities and reasons for mistrust were developed inductively by human evaluators. Subsequently, posts were assigned to these different categories by the LLM. Results Of n = 101,963 posts analyzed, 19,159 posts (18.8%) were categorized as expressing mistrust, predominantly directed at healthcare professionals (n = 14,221, 74.2%). Most common reasons for mistrust were “disregard for patient concerns” (n = 8176, 42.7%), “perceived incompetence of medical management” (n = 4871, 25.4%), and problems in “communication” (n = 4060, 21.2%). Mistrust posts commonly contained “worried” (n = 5933, 31.0%), “concerned” (n = 3623, 18.9%) and “frustrated” (n = 3046, 15.9%) tones. Conclusions Expression of medical mistrust is prevalent in social media and is predominantly directed at healthcare professionals. Mistrust is frequently associated with dismissal of patients' symptoms or concerns, a perceived lack of thoroughness in clinical management and communication difficulties, suggesting these as key actionable areas to address medical mistrust in clinical practice.
Zuerst veröffentlicht: 31. Mai 2025
Gesehen am 12.09.2025